Analysis of the structural development of production and consumption for wheat, rice and cotton in the Arab republic of Egypt - Abdel Rahman, Hosny Hafez ([s.n], 1976)
this study involves one of fundamental economical problems in egypt. the subject is extremely important nowadaysm becouse of the growing in population, and improved stability of the country depends .